Clinical development of a VAR2CSA-based placental malaria vaccine PAMVAC: Quantifying vaccine antigen-specific memory B & T cell activity in Beninese primigravidae. Issue 27 (14th June 2017) - Gbédandé, Komi; Fievet, Nadine; Viwami, Firmine; Ezinmegnon, Sem; Issifou, Saadou; Chippaux, Jean-Philippe; Dossou, Yannelle; Moutairou, Kabirou; Massougbodji, Achille; Ndam, Nicaise; de Jongh, Willem Adriaan; Søgaard, T. Max M.; et al.
Abstract: Background: The antigen VAR2CSA plays a pivotal role in the pathophysiology of pregnancy-associated malaria (PAM) caused by Plasmodium falciparum . A VAR2CSA-based vaccine candidate, PAMVAC, is under development by an EU-funded multi-country consortium (PlacMalVac project). As part of PAMVAC's clinical development, we quantified naturally acquired vaccine antigen-specific memory B and T cell responses in Beninese primigravidae recruited at the beginning of pregnancy and followed up to delivery and beyond. Methods: Clinical and parasitological histories were compiled from monthly clinic visits. On 4 occasions (first and fifth month of pregnancy, delivery, 6 months post-delivery) peripheral blood mononuclear cells were isolated for in vitro assays. PAMVAC-specific memory B cells as well as those specific for a PAM unrelated P. falciparum antigen (PfEMP1-CIDR1a) and for tetanus toxoid were quantified by ELISpot. Memory T cell responses were assessed by quantifying cytokines (IL-5, IL-6, IL-10, IL-13, IFN-γ, TNF-α) in supernatants of cells stimulated in vitro either with PAMVAC, or mitogen (PHA). Results: Both tetanus toxoid- and PAMVAC-specific memory B cell frequencies increased to reach peak levels in the 5th month and at delivery, respectively and persisted post-delivery. The frequency of CIDR1a-specific memory B cells was stable during pregnancy, but declined post-delivery. The cumulated prevalence of infection with P. falciparum during pregnancy was 61% by microscopy. In women with a history of such infections, a significantly higher frequency of PAMVAC-specific memory B cells was observed at delivery. PAMVAC-specific pro-inflammatory (IFN-γ, TNF) responses tended to be higher at delivery in those with a history of infection. Mitogen-induced IL-5/IL-13 responses were significantly enhanced in the same women. Conclusions: PAMVAC-specific memory B cells are induced during first pregnancies and are maintained post-delivery. Women with a T helper cell profile biased towards production of Th2-type cytokines have a greater risk of infection with P. falciparum.